Life history traits and leaf dynamics of the monocarpic perennial herb Saxifraga cotyledon L. - Álfur Birkir Bjarnason 1993- (2022)
Life history describes the life cycle of organisms and their trade-offs between growth, survival, and reproduction. In plants life history traits include seed size, minimum reproductive size, growth rate, reproductive effort, mortality, and longevity. In plants with monocarpic perennial life histories, resources are allocated to growth early in life, delaying reproduction. After flowering the plant dies and to compensate for lost reproductive opportunities this single reproductive event must either produce more numerous or more viable seeds. Saxifraga cotyledon is one of few sub-arctic plant species that has this kind of life history in Iceland. In the summer 2021, I marked 214 S. cotyledon plants in four cliff faces in Fljótshverfi, South-East Iceland, and recorded their density, rosette diameter, flower¬ing rate, clonal growth, and number of leaves, as well as leaf dynamics from June to October. The Icelandic population was found to have larger rosettes than a comparable Swedish population, despite similar flowering rate, highlighting the importance of growth conditions on life history traits. Strong linear relationship was found between leaf number and rosette size and substantial turnover rate of leaves was observed. Since S. cotyledon leaves are storage organs, such fast turnover is unexpected and underscores the need to inspect energy dynamics in monocarpic perennials and its impact on survival, growth rate and the evolution of monocarpic life histories. Lífsaga (e. Life history) lýsir lífsferli og fórnarskiptum lífveru með tilliti til vaxtar, lifunar og æxlunar. Hjá plöntum tekur hún m.a. til fræstærðar, lágmarksstærðar fyrir æxlun, vaxtarhraða, æxlunarátaks, dánarhraða og ævilengdar. Til að mynda geta plöntur verið fjölærar en einæxla. Þær leggja þá miklar auðlindir í upphafi lífsferils síns í vöxt en fresta blómgun og deyja að henni lokinni. Til að vega upp á móti færri æxlunar-atburðum yfir lífsleiðina þurfa fræin sem einæxla fjölærar plöntur mynda annaðhvort að vera fleiri eða lífvænlegri. Slík ...